Pneumococcal Antibody Titers - Pamella F. Abghari MD; Pavadee Poowuttikul MD; Elizabeth Secord MD, FAAAAI (SAGE Publishing, 2017)
Purpose: Immunoglobulin replacement is the mainstay treatment in patients with humoral immunodeficiencies, yet a handful of patients continue to develop sinopulmonary infections while on therapy. The objective of our study was to compare immunoglobulin G (IgG) pneumococcal antibody levels in patients with humoral immune deficiencies who have been on intravenous immunoglobulin (IVIG) replacement for at least 1 year to those on subcutaneous immunoglobulin (SCIG) therapy for at least 1 year. Methods: A retrospective chart review was completed on 28 patients. These patients' ages ranged between 1 and 61 years. Pneumococcal serotype titers obtained at least 1 year after initiating therapy were compared between patients on IVIG (19 patients) and SCIG (9 patients). Results: A comparison between the groups demonstrated that SCIG achieved a higher percentage of serotype titers protective for noninvasive disease (≥1.3) and 100% protection for invasive disease (≥0.2). Our data also demonstrated a similar lack of protection (less than 50% ≥1.3) in 9N, 12F, and 23F on IVIG and 4, 9N, 12F, and 23F on SCIG. Conclusions: Our data demonstrated that serotypes 1, 3, 4, 9N, 12F, and 23F exhibited the lowest random IgG means while on IVIG, which was comparable to other published studies that looked at the mean IgG levels. In addition, our retrospective chart review demonstrated a greater number of therapeutic pneumococcal titers with SCIG in comparison to IVIG.